2017
DOI: 10.1016/j.taap.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor deficiency reduces liver fibrosis in mice

Abstract: Liver diseases are associated with complex changes in the hemostatic system and elevated levels of the platelet-adhesive protein Von Willebrand factor (VWF) are reported in patients with acute and chronic liver damage. Although elevated levels of VWF are associated with fibrosis in the general population, the role of VWF in acute and chronic liver injury has not been examined in depth in experimental settings. We tested the hypothesis that VWF deficiency inhibits experimental liver injury and fibrosis. Wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…12 It is most common in elderly patients with type 2 or 3 VWD. 12,13 The presenting patient had history of gastrointestinal bleeding in the form of haematemesis and melena. During admission, the child was well thriving, moderately pale, multiple bruises over extremities, and she had no active bleeding from any site.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is most common in elderly patients with type 2 or 3 VWD. 12,13 The presenting patient had history of gastrointestinal bleeding in the form of haematemesis and melena. During admission, the child was well thriving, moderately pale, multiple bruises over extremities, and she had no active bleeding from any site.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis was quantified with multiple complementary approaches as described previously . Staining of formalin‐fixed paraffin‐embedded liver sections to assess hepatic fibrosis was performed by the MSU Investigative Histopathology Laboratory, a division of Human Pathology.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of α‐smooth muscle actin (αSMA) was detected by immunohistochemical labeling of paraffin‐embedded liver tissues as described previously . For quantification of the total area of PSR and αSMA staining, slides were first scanned by use of a Virtual Slide System VS110 (Olympus, Waltham, MA, USA) with a 20× objective, and sample images were then digitally captured from the entire left lateral lobe (Visiopharm, Broomfield, CO, USA) as described previously . The total area of positive staining was calculated in an unbiased fashion from 200 images per slide (captured with a 10× virtual objective) by use of a batch macro and color deconvolution tool in imagej fiji .…”
Section: Methodsmentioning
confidence: 99%
“…43 Depletion of VWF in in vivo mice models of acute liver injury resulted in decreased liver fibrosis. 44 In contrast, ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13), a VWF cleaving enzyme, is often decreased in cirrhosis. A study evaluating the effects of ADAMTS13 in a mouse model of nonalcoholic fatty liver disease demonstrated that ADAMTS-13 deficiency led to increased fibrosis and microthromboses in the liver.…”
Section: Mechanism Of Thrombosis and Role Of Doacs As Antifibrotic Agmentioning
confidence: 99%